Tingkat Kerusakan Lahan Akibat Penambangan Mineral Non-Logam dan Batuan di Daerah Semin, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta dengan Metode Tanpa Pembobotan - Doni Ardiansyah (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2020)
Mining activities are often blamed for causing land damage. Land damage that occurs can be monitored, so it can be controlled and repaired. This research was conducted in the Semin area, Gunungkidul Regency, Yogyakarta Special Region, from November 2017 to March 2018. The Semin area has a lot of rock mining activities and in border of provinces. Therefore, the study of land damage caused by mining activities in this area is deemed very important. The purpose of this study was to determine and study the conditions of land damage caused by mining activities during the research period. The method used in this research is a weightless method from several parameters which mostly refers to the Yogyakarta Governor Decree Number 63 of 2003 as the observed parameters, that is 1) The character of rock compilation, 2) rock fracturing level 3) Utilization and management of top soil, 4) Depth of excavation / height of wall, 5) Limit of slope of excavation, 6) Reclamation time, 7) Amount of erosion, 8) River flow / sedimentation. The data is processed by using the weightless method, where all parameters have the same weight. The level of damage is divided into three, based on the value, namely 1) Good (1.00-1.66), 2) Medium (1.67 - 2.33), and 3) Damaged (2.34 - 3.00). The total observed mine sites were 81 mine sites. There are 21 mine sites that are included in the Good category, 60 mine sites that are included in the Medium category, and no mine sites are in the Damaged category